The Importance of labeling products with a GMO or non-GMO label - Meško Kuralt, Katja (Medicine, Law & Society, 2021)
The article is based on publicly available data, namely on European legislation and on publicly available instructions or recommendations/guidelines dealing with the field of GMO labelling in Slovenia. Using a comparative research method, the importance of labelling GMO-free products and GMO-labelled products was analysed. The analysis is based on a comparison of the basic terms with each other (i.e., GMO-labelled products, non-GMO-labelled products), based on a review of the legal definition of the terms and based on control over the use of the terms. The purpose of this paper is to define an important difference between the two concepts, which is hidden and (or) not defined for most consumers.